The role of radiotherapy and intrathecal CNS prophylaxis in extralymphatic craniofacial aggressive B-cell lymphomas - Murawski, Niels Michael; Witzens-Harig, Mathias (Blood, 2014)
To define the role of radiotherapy and intrathecal prophylaxis in extralymphatic craniofacial involvement (ECFI) of aggressive B-cell lymphoma, we analyzed 11 consecutive German High-Grade Non-Hodgkin Lymphoma Study Group trials. ECFI occurred in 290/4155 (7.0%) patients (orbita, 31; paranasal sinuses, 93; main nasal cavity, 38; tongue, 27; remaining oral cavity, 99; salivary glands, 54). In a multivariable analysis adjusted for International Prognostic Index rituximab improved event-free and overall survival both in patients with and without ECFI. Three-year event-free (79% vs 79%; P = .842) and overall survival (86% vs 88%; P = .351) rates were similar in 145 patients receiving and 57 not receiving radiotherapy. Without rituximab, the 2-year cumulative rate of central nervous system (CNS) disease was increased in 205 ECFI patients compared with 2586 non-ECFI patients (4.2% vs 2.8%; P = .038), whereas this was not observed with rituximab (1.6% in 83 ECFI vs 3.4% in 1252 non-ECFI patients; P = .682). In 88 ECFI patients who received intrathecal prophylaxis with methotrexate, the 2-year rate of CNS disease was 4.2% compared with 2.3% in 191 patients who did not (P = .981). In conclusion, rituximab eliminates the increased risk for CNS disease in patients with ECFI. This retrospective analysis does not support intrathecal prophylaxis or radiotherapy to ECFI patients in complete remission/unconfirmed complete remission. These findings should be confirmed in a prospective study.